Acute Effects of Different Intensities of Cycling Acute Exercise on Carotid Arterial Apparent Elasticity and Hemodynamic Variables. (9th November 2020) - Shen, Bing-Yi; Liu, Hai-Bin; Cao, Ling; Qin, Kai-Rong
Abstract : Background . Cardiovascular disease (CVD) is closely related to arterial elasticity and hemodynamics. Exercises have been reported to immediately decrease arterial apparent elasticity and regulate hemodynamic variables. However, the relationship between them and exercise intensity remains elusive. The purpose of this study was to determine the acute effects of different intensities of acute cycling exercise on carotid arterial apparent elasticity and hemodynamics. Methods . 32 healthy men (age: 19.4 ± 0.6 years) attended the laboratory on five occasions and completed cycling acute exercise for 20 minutes at five intensities (40%, 50%, 60%, 70%, and 80% heart rate reserve (HRR)). At the right carotid artery, center-line velocity and arterial inner diameter waveforms were examined before and immediately after exercise. Based upon the measured data, the classical hemodynamic theory was used to calculate the apparent elasticity and the local hemodynamic variables. Results . The arterial apparent stiffness and the apparent elastic modulus following acute cycling exercise at 60% to 80% HRR were significantly higher than baseline. The mean center-line velocity accelerated from 50% to 80% HRR, but no intensity of intervention altered mean blood flow. Immediately after intervention, the mean wall shear stress and oscillatory shear index increased. Conclusions . Aerobic cycling intervention, with intensity from 40% to 80% HRR, did not change the brain blood supply. A bout of cycling intervention decreased apparent elasticity, and there was an intensity-dependent effect on apparent elasticity and hemodynamic variables. This study would provide referable data for the further study on the effects of aerobic exercise on arterial hemodynamics and elasticity and underlying physiological mechanisms.